Dialética no ceticismo pirrônico: a contribuição da sofística no corpus argumentativo cético - Porto, Wesley Rennyer Martins Rabelo (2016)
The investigations carried out for this work aim at reflecting about the nature of the pyrrhonian discourse, and, at the same time, at trying to comprehend the sophistic‟s contribution to the formation of certain skeptical argumentative procedures. Initially, the historical development of skepticism will be traced, including, at this stage, the moment preceding the formation of the skeptical tradition as school, i.e., the moment called proto-skepticism, which bursts out still during the pre-Socratic period. Afterwards, a critical-comparative analysis between sophistry and skepticism will be started, focusing on the thoughts of the sophists Protagoras of Abdera and Gorgias of Leontini. Here we will see how some of these sophists‟ theoretical formulas and theses anticipated some of the most significant principles and arguments of the pyrrhonian tradition. Finally, the investigation addresses the skeptical discourse itself, as the fundamental characteristics and the identitary elements of the pyrrhonian logos will be examined. Especially at this point, the search for the crucial components of the skeptical discourse will be grounded on Sextus Empiricus‟s writings, the richest and most important sources about greek skepticism. We shall have, thus, a meticulous dialogue with this pyrrhonian author, in order to extract the main features of the skeptical discourse.